SUASANA KEHIDUPAN MASYARAKAT DI SEKITAR SUNGAIBATANGHARI DALAM SENI LUKIS POST IMPRESIONIS - Rahmad, Yasrul Sami B, S.Sn., M.Sn. Drs. Syafwan, M.Si. (Universitas Negeri Padang, 2018)
The purpose of the creation of this final paper is to visualize and expressthe atmosphere of community life around the river Batanghari in post impressionist painting in the hope to be able to maintain its existence so as not to be forgotten, so that the public can better know and understand the importance of maintaining the environment, especially on the banks of the river Batanghari.The methods used are: first preparation, looking for 1art ideas based on Batanghari river references from various media and surveys through interviews with some resource persons. Both elaborations, analyzing data. third synthesis, set the idea. Fourth realization of concept, taking photos. The five stages of completion, the implementation of the exhibition, documentation, and reports of painting post impressionism. The author displays how the activities of people who are in the river Batanghari.Ten post impressionist paintings describe the activities of people in the river Batanghari. The work outlines how the daily life of the community around the Batanghari river includes the activity and atmosphere around the river Batanghari. The tenth work include: 1). Rumahku, 2). Menyeberang, 3). Mendulang Emas, 4). Aktivitasku, 5). Nelayan 6). MCK, 7). Menambang Pasir, 8). Speed Boat, 9). Keramba Ikan, 10). Menambang Batu.